An eye tracking study of the application of gestalt theory in photography - Hsien-Chih Chuang; Han-Yi Tseng; Da-Lun Tang (Bern Open Publishing, 2023)
Photography is an art form where integration of the human visual perception and psychological experiences result in aesthetic pleasure. This research utilizes eye tracking to explore the impact of the properties of Gestalt in photography on people's visual cognitive process in order to understand the psychological processes and patterns of photography appreciation. This study found that images with Gestalt qualities can significantly affect fixation, sightline distribution, and subjective evaluation of aesthetics and complexity. Closure composition images seem to make cognition simpler, resulting in the least number of fixation and saccades, longer fixation duration, and more concentrated sightline indicating stronger feeling of beauty, while images which portray similarity results in the greatest fixation and saccades, longest saccade duration, and greater scattering of sightline, indicating feelings of complexity and unsightliness. The results of this research are closely related to the theories of art and design, and have reference value for photography theory and application.